Argumentation by Parable in Matthew 24–25 as Parrhesia - Lahti, Niilo (Journal of early Christian history, 2024)
Parables offer Jesus a chance to discuss bold and difficult topics even in hostile situations. In this sense, telling parables represents parrhesia (παρρησία) as it increases freedom of speech. Surprisingly, he resorts to such a strategy with his followers when arguing about the Son of Man’s inspection in Matthew 24–25. What bold message demands such indirect argumentation by parable? Reconstructing the argumentation structure with pragma-dialectics reveals the overall standpoint: It is unlikely to survive the inspection of the Son of Man. The approach uncovers how the parables function as arguments and gradually build support for the standpoint. Through gradual and indirect unveiling of the overall message, the disciples may infer and accept the distressing outcome. The article investigates the extent to which aspects of parrhesia are included in the argumentation by parable in Matthew 24–25.